2020
DOI: 10.3389/fonc.2020.604121
|View full text |Cite
|
Sign up to set email alerts
|

Glioblastoma Organoids: Pre-Clinical Applications and Challenges in the Context of Immunotherapy

Abstract: Malignant brain tumors remain uniformly fatal, even with the best-to-date treatment. For Glioblastoma (GBM), the most severe form of brain cancer in adults, the median overall survival is roughly over a year. New therapeutic options are urgently needed, yet recent clinical trials in the field have been largely disappointing. This is partially due to inappropriate preclinical model systems, which do not reflect the complexity of patient tumors. Furthermore, clinically relevant patient-derived models recapitulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 148 publications
(256 reference statements)
0
54
0
Order By: Relevance
“…Furthermore, in vitro cell culture does not model human immune cells. This limits exploration of factors regulating tumor-host interactions and immune control (21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in vitro cell culture does not model human immune cells. This limits exploration of factors regulating tumor-host interactions and immune control (21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro, glioblastoma cells can also be cultivated as 3D spheroids or organoids [ 165 , 166 , 167 , 178 ]. As in 2D cultures, the tumor-surrounding microenvironment is absent.…”
Section: Preclinical Models To Study Glutamate Interaction and Tumor-associated Epilepsymentioning
confidence: 99%
“…As in 2D cultures, the tumor-surrounding microenvironment is absent. Co-culture models and approaches with limited immune components exist, but these may only reflect selected components and are no full replacement for in vivo conditions [ 166 ]. With respect to glutamate-driven processes in glioblastoma, the main focus with these models is on drug screening and as a source for injection in in vivo models or in organotypic brain slices.…”
Section: Preclinical Models To Study Glutamate Interaction and Tumor-associated Epilepsymentioning
confidence: 99%
“…Dijkstra et al established a co-culture system of autologous tumor organoids and peripheral blood lymphocytes of patients to induce and analyze tumor-specific T cell responses for mismatch repair deficient colorectal cancer and non-small cell lung cancer in a personalized manner [ 118 ]. Klein et al demonstrated the advantages of co-culture systems of GBM organoids and human immune cells, to investigate not only immune–tumor interactions, but also to explore current and novel immunotherapies, such as adoptive T cell transfer, immune checkpoint inhibitors, or oncolytic viruses [ 127 ].…”
Section: Integration Of Intra-tumor Heterogeneity Into Multi-layered Personalized Cancer Therapymentioning
confidence: 99%